Pulmonary expression of CYP2A13 and ABCB1 is regulated by FOXA2, and their genetic interaction is associated with lung cancer. Issue 5 (9th February 2015) - Xiang, Chan; Wang, Jiucun; Kou, Xiaochen; Chen, Xiabin; Qin, Zhaoyu; Jiang, Yan; Sun, Chang; Xu, Jibin; Tan, Wen; Jin, Li; Lin, Dongxin; He, Fuchu; et al.
ABSTRACT: Inhaled xenobiotics such as tobacco‐specific carcinogen 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone are mainly metabolized by phase I oxidase cytochrome P450, family 2, subfamily A, polypeptide 13 (CYP2A13), phase II conjugate UDP glucuronosyltransferase 2 family, polypeptide B17 (UGT2B17), and phase III transporter ATP‐binding cassette, subfamily B (MDR/TAP), member 1 (ABCB1), with genetic polymorphisms implicated in lung cancer. Their genetic interaction and pulmonary expression regulation are largely unknown. We analyzed joint association for CYP2A13 and ABCB1 polymorphisms in 2 independent lung cancer case populations (669 and 566 patients) and 1 common control population (749 subjects), and characterized the transacting function of the lung development‐related transcription factor forkhead box A2 (FOXA2). We undertook FOXA2 overexpression and down‐regulation in lung epithelial cell lines, analyzed functional impact on the trans‐activation of CYP2A13, UGT2B17, and ABCB1, and measured correlation for their expressions in lung tissues. We found a substantial reduction in cancer risk (OR 0.39; 95% CI 0.25‐0.61; P interaction = 0.029) associated with combined genotypes for CYP2A13 R257C and a functionary regulatory variant in the cis element of ABCB1 synergistically targeted by GATA binding protein 6 and FOXA2. Genetic manipulation of FOXA2 consistently influenced its binding to and transactivation of the promoters of CYP2A13, UGT2B17, and ABCB1, whose mRNA and protein expressions were all consistently correlated with those of FOXA2 in both tumorous and normal lung tissues. We therefore establish FOXA2 as a core transcriptional modulator for pulmonary xenobiotic metabolic pathways and uncover an etiologically relevant interaction between CYP2A13 and ABCB1, furthering our understanding of expression and function of the xenobiotic metabolism system.—Xiang, C, Wang, J., Kou, X., Chen, X., Qin, Z., Jiang, Y., Sun, C., Xu, J., Tan, W., Jin, L., Lin, D., He, F., Wang, H. Pulmonary expression of CYP2A13 and ABCB1 is regulated by FOXA2, and their genetic interaction is associated with lung cancer. FASEB J. 29, 1986‐1998 (2015). www.fasebj.org